Clinical Findings and Molecular Diagnosis of Retinoblastoma in Older Children. (3rd January 2013) - Sheck, Leo H. N.; Ng, Yvonne S. P.; Watson, Mike; Vincent, Andrea L.
Abstract: Background : Retinoblastoma (RB) is the most common primary childhood intraocular malignancy and usually presents before the age of 4 years. RB in late childhood is rare and may pose a diagnostic challenge to clinicians. Materials and Methods : Patients over the age of 4 years with RB were identified retrospectively. Clinical data, histological findings, and molecular genetic diagnoses were obtained. Results : Two cases of late onset RB were identified. Case 1 was a 10-year-old boy who presented with floaters, and was found to have a unilateral exudative retinal detachment and RB on clinical examination. Genetic testing showed a novel homozygous mutation in exon 20 of the RB1 gene in the tumor sample, c.2027_2034dup, resulting in p.Ile679X. No mutation was found in the DNA obtained from the peripheral blood sample. Case 2 was a 6-year-old boy who presented with loss of vision and pain in the left eye. RB was diagnosed on clinical examination with exudative retinal detachment. Genetic testing showed no mutation in the RB1 gene, but complete methylation of the RB1 promoter region. Conclusions : RB can rarely present in late childhood. Clinicians should consider RB as a diagnosis when faced with a patient with unexplained exudative retinal detachment.